THE RISE OF PERSONALIZATION IN MARKETING: HOW BRANDS ARE TAILORING THEIR STRATEGIES TO INDIVIDUAL CUSTOMERS - Anorboyeva Durdona Dilshodovna (Web of Journals Publishing, 2023)
This article explores the burgeoning prominence of personalization within the realm of marketing, investigating the strategic adaptations employed by brands to tailor their approaches according to the unique characteristics and preferences of individual customers. The evolution of consumer expectations and technological advancements have converged to propel the adoption of personalized strategies, reshaping traditional marketing paradigms. Through an examination of key methodologies and real-world cases, this study delineates the diverse mechanisms through which brands are harnessing data-driven insights, advanced analytics, and innovative communication channels to forge deeper connections with their audience. By dissecting the pivotal drivers behind this trend, the article offers insights into the symbiotic relationship between personalization and customer engagement, shedding light on its transformative potential for the future of marketing practices.
Keywords: Personalization, Marketing, Tailoring, Strategies, Individual Customers.